AKTIVITAS ANTIBAKTERI SENYAWA GOLONGAN TRITERPENOID DARI BIJI PEPAYA (Carica papaya L.) - Sukadana, I M.; Rahayu Santi, Sri; Juliarti, N. K. (Jurnal Kimia (Journal of Chemistry); Vol. 2, No. 1 Januari 2008, 2012)
Isolation, identification, and antibacterial activity examination have been conducted for triterpenoids compounds of carica papaya L. Maseration of 500 g pawpaw seed powder in n-hexane gave 21.66 g extract which reacts with Liebermann-Buched reagent resulting in colour change (yellow to purple). Column chromatography separation of the extract resulted in 0.05 g yellow isolate (F3) which contains aldehyde triterpenoids. Infrared spectra indicated aliphatic –C-H stretching, -CH2 bending, -CH3 bending, and C=O. Ultra violet – visible spectra showed absorption at 228.5 nm and proad peak at 287.7 nm. Antibacterial axamination showed that 1000 ppm at the isolate inhibits the growth of Escherichia coli and Staphylococcus auerus.
Keywords: isolation, triterpenoid, pawpaw seed, antibacterial